Research of Explode Exposure at the Relief Vent System Structures with Soft Transparent Material - Pozdieiev, Serhii; Pidgoretskiy, Yuriy; Nekora, Olga; Sidnei, Stanislav; Tyshchenko, Oleksandr (International Journal of Engineering and Technology, 2018)
A methodology was developed for studying the influence of structural parameters of the relief panels of flexible fencing elements on their behavior in case of explosion. A mathematical model was substantiated on the influence of structural parameters of relief panels with flexible fencing elements on the conditions of their triggering, based on the theory of plates and shells. There was also developed a method for determining the structural parameters for the successful triggering of the relief panels with flexible elements of fencing in case of excessive pressure of explosion, exceeding the maximum allowed parameters.Â